2020
DOI: 10.4102/sajhrm.v18i0.1247
|View full text |Cite
|
Sign up to set email alerts
|

Psychological capital and organisational citizenship behaviour in selected public hospitals in the Eastern Cape Province of South Africa

Abstract: Orientation: The relationship between psychological capital (PsyCap) and organisational citizenship behaviour (OCB) is important to establish especially in the South African public hospitals where the quality of healthcare services have been reported to have deteriorated.Research purpose: The purpose of this study was to examine the relationship between psychological capital and organisational citizenship behaviour among nurses in the public hospitals.Motivation for the study: There is crisis in the public nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 88 publications
3
16
0
Order By: Relevance
“…This means that Psycap can be a vital asset for teachers to develop their OCB. These findings confirm scholarly studies in which PsyCap was found to be related to OCB ( Yildiz 2019 ; Chamisa et al 2020 ; Rodríguez-Cifuentes et al 2020 ; Da et al 2021 ). In reality, PsyCap indicators, such as self-efficacy, optimism, hope, and resilience ( Luthans and Youssef-Morgan 2017 ), are essential antecedents for teachers to build altruism, conscientiousness, sportsmanship, courtesy, and civic virtue ( Organ et al 2006 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This means that Psycap can be a vital asset for teachers to develop their OCB. These findings confirm scholarly studies in which PsyCap was found to be related to OCB ( Yildiz 2019 ; Chamisa et al 2020 ; Rodríguez-Cifuentes et al 2020 ; Da et al 2021 ). In reality, PsyCap indicators, such as self-efficacy, optimism, hope, and resilience ( Luthans and Youssef-Morgan 2017 ), are essential antecedents for teachers to build altruism, conscientiousness, sportsmanship, courtesy, and civic virtue ( Organ et al 2006 ).…”
Section: Discussionsupporting
confidence: 89%
“…To achieve this goal, using SEM analysis and research participants among teachers in Indonesia, we seek to confirm results from previous studies, which are used as the basis for building the research hypotheses of this study—namely the influence of cultural intelligence on interpersonal communication ( Bostan et al 2021 ), PsyCap ( Chen and Chen 2018 ), and OCB ( Shafieihassanabadi and Pourrashidi 2019 ). Then, we uncover the influence of interpersonal communication on OCB ( Nofia et al 2019 ; Syamsudin and Retnowati 2019 ) and the influence of PsyCap on OCB ( Chamisa et al 2020 ; Rodríguez-Cifuentes et al 2020 ; Da et al 2021 ). Finally, we hope to find the relationship between cultural intelligence and OCB, mediated by interpersonal communication and PsyCap, in order to build novel and relevant models from our research results.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…P. Podsakoff, Whiting, Podsakoff, & Blume, 2009). Some positive associations have been found between PsyCap and AOC (Avey, Luthans, & Youssef, 2010;C¸etin, 2011;Lather & Kaur, 2015), and also between PsyCap and OCB (Chamisa, Mjoli, & Mhlanga, 2020;Norman, Avey, Nimnicht, & Graber Pigeon, 2010). Despite that dearth, research has begun to examine potential mediators of the PsyCap-outcomes relationships such as psychological empowerment (Avey, Hughes, Norman, & Luthans, 2008) and work engagement (Gupta et al, 2017).…”
mentioning
confidence: 99%
“…When employees were hopeful, confident, optimistic, and resilient, they would achieve more (Ribeiro et al, 2021). These positive personal resources would help in developing the organizational citizenship behaviour for organizations, as well as individuals (Chamisa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%